The big friendly counter-space? Interreligious encounter within social media - Neumaier, Anna (Religion, 2020)
Research on interreligious dialogue mostly focuses on face-to-face meetings, however, it also takes place in other contexts. Among them is the huge space of interactive media, where adherents of different religious traditions meet, e.g., in interreligious groups on Facebook, boards or commentary sections - but so far little has been researched on this field. The article is an explorative attempt to sort the field of interreligious dialogue and encounter in social media, drawing on a comparative perspective on the field of offline interreligious dialogue. For this purpose, it first gives a systematizing overview of the existing research on interreligious encounter in social media as well as on (offline) interreligious dialogue, identifying key questions and issues on interreligious encounter. Examples from different social media platforms then allow conclusions about commonalities and differences between online and offline interreligious encounter and suggest crucial aspects to follow up on in future research on this field.